Cr, Cu, Hg and Ni release from incineration bottom ash during utilization in land reclamation – based on lab-scale batch and column leaching experiments and a modeling study. (April 2018) - Yin, Ke; Chan, Wei Ping; Dou, Xiaomin; Ren, Fei; Wei-Chung Chang, Victor
Abstract: Incineration bottom ash (IBA) as potential material for land reclamation was investigated, based on leaching tests, sorption studies and simulation models. Based on batch and column leaching tests, Cr, Cu, Hg and Ni in the IBA leachates were measured as high as 510 μg/L, 20330 μg/L, 5.1 μg/L and 627 μg/L, respectively, presenting potential environmental risks. Sorption study was then performed with various concentrations of IBA leachates on sands and excavated materials. Partitioning coefficients of targeting metals were determined to be 6.5 (Cr), 18.4 (Cu), 16.6 (Hg), and 1.8 (Ni) for sands, while 17.4 (Cr), 13.6 (Cu), 67.1 (Hg), and 0.9 (Ni) for excavated materials, much lower than literature in favor of their transportation. Deterministic and Monte Carlo simulation was further performed under designated boundaries, combined with measured geotechnical parameters: density, porosity, permeability, partitioning coefficient, observed diffusivity, hydraulic gradient, etc., to quantitatively predict metals' fate during IBA land reclamation. Environmental risks were quantitatively unveiled in terms of predicted time of breakthrough for the targeting metals (comparing to US EPA criterion for maximum or continuous concentration). Sands were of little effects for all metals' breakthrough (1 month or less) under advection, while excavated materials sufficiently retained metals from thousands up to millions of years, under diffusion or advection. Permeability next to the IBA layer as the major risk-limiting factor, dominated transport of IBA leachates into the field. The current study provides discrimination of environmental risks associated with metals and a quantitative guidance of project design for IBA utilization in land reclamation. Highlights: Permeability stands as the major risk-limiting factor for IBA land reclamation. Sand is ineffective for metal breakthrough under advection at d h /d x  = 0.05 m/m. Excavated material retains metals under limits at least for a few thousand years.